Fast isolation of hydrophobic organic environmental contaminants from exposed semipermeable membrane devices (SPMDs) prior to GC analysis - Setková, Lucie; Hajslová, Jana; Bergqvist, Per-Anders; Kocourek, Vladimír; Kazda, Radek; Suchan, Petr (Journal of chromatography. A, 2005)
Semipermeable membrane devices (SPMD) represent a passive sampling technology that is becoming widely used for monitoring of surface waters pollution. While "classic" procedures employ dialysis to recover target compounds from exposed SPMDs, in the present study analytes were isolated from cut membrane together with sequestering medium (triolein) using hexane as an extraction solvent. This approach allowed us to reduce the time needed for accomplishment of isolation step from 48 h to only 1 h. Automated gel permeation chromatography (GPC) clean-up is employed in the following step to separate triolein from analytes fraction. Musk compounds (MCs), polychlorinated biphenyls (PCBs), brominated flame retardants (BFRs) and several other persistent organochlorine compounds (OCs) were determined in the respective fraction by GC method employing selective detectors (MSD, ECD). As shown in a series of analyses of SPMDs deployed in various aquatic ecosystems, high recoveries and good repeatability of results together with a possibility to obtain the information on the pollution of sampling site at the day of sample arrival to laboratory make this newly implemented procedure an interesting alternative to time consuming dialysis.
Keywords: Chromatography, Gas; Environmental Pollutants; chromatografie plynová; Chromatography, Gel; látky znečišťující životní prostředí; Permeability; Membranes, Artificial; Reference Standards; organické látky; Organic Chemicals; referenční standardy; membrány umělé; permeabilita; gelová chromatografie